The Impact of Product Quality, Pricing, and Location on Consumer Buying Decisions: A Case Study of Faris Restaurant in Palopo City - Paembong, Lois Randa; Ramadhan, Muh. Hilal; Nurfadilla, Andi; Nurjannah, Nurjannah; Mahmut, Cici (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine the influence of product quality, price, and location on consumer purchasing decisions, using Faris Restaurant in Palopo City as a case study. As competition in the culinary industry intensifies, especially in urban centers, understanding the key factors that drive customer choice is essential for business sustainability. A quantitative approach was employed, involving surveys, interviews, and observations with a sample of 36 respondents. Data were analyzed using multiple linear regression, with partial (t-test) and simultaneous (f-test) significance testing. The partial test results revealed that individually, product quality, price, and location did not significantly influence purchasing decisions. However, the simultaneous test showed that when these three variables were considered together, they had a statistically significant effect on consumer decisions. Among the variables, location was found to be the most influential factor, suggesting that accessibility and environmental comfort are crucial to consumer preference. These findings imply that consumers base their dining choices on a combination of factors rather than a single aspect. The study concludes that Faris Restaurant should adopt an integrated marketing strategy that balances consistent food quality, fair pricing, and optimal location management. The results provide valuable insights for culinary businesses aiming to enhance competitiveness and consumer satisfaction in a rapidly evolving market.